Association between preadmission frailty and care level at discharge in older adults undergoing emergency laparotomy. Issue 3 (10th January 2020) - Carter, B; Law, J; Hewitt, J; Parmar, K L; Boyle, J M; Casey, P; Maitra, I; Pearce, L; Moug, S J; Ross, Bryony; Oleksiewicz, Julia; Fearnhead, Nicola; et al.
Abstract: Background: Older adults undergoing emergency abdominal surgery have significantly poorer outcomes than younger adults. For those who survive, the level of care required on discharge from hospital is unknown and such information could guide decision-making. The ELF (Emergency Laparotomy and Frailty) study aimed to determine whether preoperative frailty in older adults was associated with increased dependence at the time of discharge. Methods: The ELF study was a UK-wide multicentre prospective cohort study of older patients (65 years or more) undergoing emergency laparotomy during March and June 2017. The objective was to establish whether preoperative frailty was associated with increased care level at discharge compared with preoperative care level. The analysis used a multilevel logistic regression adjusted for preadmission frailty, patient age, sex and care level. Results: A total of 934 patients were included from 49 hospitals. Mean(s.d.) age was 76·2(6·8) years, with 57·6 per cent women; 20·2 per cent were frail. Some 37·4 per cent of older adults had an increased care level at discharge. Increasing frailty was associated with increased discharge care level, with greater predictive power than age. The adjusted odds ratio for an increase in care level was 4·48 (95 per cent c.i. 2·03 to 9·91) for apparently vulnerable patients (Clinical Frailty Score (CFS) 4), 5·94 (2·54 to 13·90) for those mildly frail (CFS 5) and 7·88 (2·97 to 20·79) for those moderately or severely frail (CFS 6 or 7), compared with patients who were fit. Conclusion: Over 37 per cent of older adults undergoing emergency laparotomy required increased care at discharge. Frailty scoring was a significant predictor, and should be integrated into all acute surgical units to aid shared decision-making and discharge planning. Graphical Abstract: This UK-wide prospective cohort study of 934 patients (from 49 hospitals) aged 65 years or older undergoing emergency laparotomy found that increased frailty was associated with a reduction in independence at discharge, compared with admission care level. CFS, Clinical Frailty Score. Frailty predicts outcomes